Jet in Supersonic Crossflow - Sun, Mingbo; Wang, Hongbo; Xiao, Feng.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
Based on research into jets in supersonic crossflow carried out by the authors' team over the past 15 years, this book summarizes and presents many cutting-edge findings and analyses on this subject. It tackles the complicated mixing process of gas jets and atomization process of liquid jets in supersonic crossflow, and studies their physical mechanisms. Advanced experimental and numerical techniques are applied to further readers' understanding of atomization, mixing, and combustion of fuel jets in supersonic crossflow, which can promote superior fuel injection design in scramjet engines. The book offers a valuable reference guide for all researchers and engineers working on the design of scramjet engines, and will also benefit graduate students majoring in aeronautical and aerospace engineering.
Introduction -- Spatial distribution of gaseous jet in supersonic crossflow -- Flow structures of gaseous jet in supersonic crossflow -- Mixing characteristics of gaseous jet in supersonic crossflow -- Combustion characteristics of gaseous jets in the supersonic crossflow -- Liquid jet primary breakup in supersonic crossflow.
Keywords: Fluid mechanics; Continuum mechanics; Aerospace engineering; Astronautics; Engines; Engineering mathematics; Engineering -- Data processing; Mathematical physics; Engineering Fluid Dynamics; Continuum Mechanics; Aerospace Technology and Astronautics; Engine Technology; Mathematical and Computational Engineering Applications; Theoretical, Mathematical and Computational Physics